(untitled) (World Journal of Current Medical and Pharmaceutical Research, 2026)
Dermatological manifestations are common adverse effects observed in patients undergoing cancer treatment, particularly in those with solid tumours receiving chemotherapy and targeted therapy. Solid tumours represent a major group of malignancies, and their management often involves systemic therapies that can affect rapidly dividing cells, including those of the skin, hair, and nails. These treatment-related dermatological changes can vary in pattern and severity, and their high prevalence can significantly impact patients’ quality of life and treatment adherence. Understanding the patterns, prevalence, and clinical implications of these manifestations is important for early recognition and effective management, thereby improving overall patient care.The study aimed to determine the prevalence and describe the patterns of dermatological manifestations in patients with solid tumours receiving chemotherapy and targeted therapy. It also aimed to assess the severity of these manifestations using CTCAE grading and to evaluate their association with treatment modality and number of chemotherapy cycles.A prospective observational study was conducted on 100 patients with histologically confirmed solid tumours receiving chemotherapy and targeted therapy. Data were collected on demographic characteristics, cancer type, stage, treatment modalities, and dermatological manifestations. Severity was assessed using CTCAE grading. Statistical analysis was performed using descriptive statistics, and Chi-square test was applied to determine associations between variables. Adjuvant chemotherapy was the most commonly used treatment modality. The majority of patients received 3–5 cycles of chemotherapy. Paclitaxel and carboplatin were the most frequently used chemotherapeutic agents. Dermatological manifestations were observed in 87% of patients. Alopecia was the most common manifestation, followed by xerosis, hyperpigmentation, and melanonychia. The mean number of dermatological manifestations per patient was 1.91 ± 1.28. Most dermatological toxicities were of mild to moderate severity (Grade 1 and Grade 2). Only a small proportion of patients required dermatology referral (24%) and treatment modification (7%). No statistically significant association was observed between treatment modality (p = 0.652) or number of chemotherapy cycles (p = 0.618) and dermatological toxicity. Conclusion- Dermatological manifestations are highly prevalent among patients receiving chemotherapy and targeted therapy, with most experiencing multiple manifestations. The majority are mild to moderate and manageable with supportive care. Early recognition and management improve patient comfort and treatment adherence.